NILAI PENDIDIKAN DALAM NOVEL MY LOVE IS A WHITE HACKER KARYA MAHMUD JAUHARI ALI - Rachmasisca, Frieska Maryova (STKIP PGRI Bandar Lampung, 2018)
The problem of analyzing a novel literary work is that the mastery of every reading material must be mastered in depth each verse by verse. This is done to obtain an object of study will be examined in a study of literature. The purpose of the study are to know and analyze the educational values contained in the novel My Love Is A White Hacker by Mahmud Jauhari Ali. The method used in this study is descriptive qualitative method to analyze the value of education contained in the novel. The principal technique used by the author to collect data is by reading, understanding, and analyzing Mahmud Jauhari Ali's novel, My Love Is A White Hacker. Step analysis of the data by reading the novel carefully, summarizing the content or meaning, re-reading the novel intensively, describe and analyze the values of education and draw conclusions of educational values contained in the novel. The results of the analysis of the educational value data of My Love Is A White Hacker's novel by Mahmud Jauhari Ali, namely the value of social education, such as help, empathy and togetherness, the value of religious education such as gratitude, truth value, moral education value such as honesty.